The migration of doctors following Iceland’s economic collapse. Is Iceland facing a brain drain? - Kerul, Alina, 1976- (2012)
Since the middle of the 20th century, many theories on migration patterns have been developed and tested. Most of this analytical work examines general population migration patterns with respect to the micro- and macro- economic situations of source and destination countries. But at the same time not many of them concentrate on the level of education, and skills of the migrating population. This also applies to the research that has been done in Iceland. This is not surprising due to the data shortage. In my research I want to exam the doctors’ international migration after the 2008 recession, so that on my results I will be able to answer the following question: ,,Is Iceland facing a brain drain when it comes to the medical profession?”. This research is based on data that I received from the Læknafélag Íslands, which I then compare with migration patterns for the general population. The main result of this research is – the doctors’ migration rates are significantly higher than general population rates in particular for the younger doctors. Moreover, their main destination countries are Sweden and Norway. On that basis, I am concluding that Iceland does in fact suffer from brain drain in the medical profession.